PENINGKATAN BERPIKIR KRITIS MELALUI MEDIA WORDWALL DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI KELAS III SD NEGERI 066055 MEDAN DENAI - Ikmal Muslimah Br Pasaribu; Ambar Wulan Sari; Hotnida Simarmata (STKIP Subang, 2024)
The implementation of learning that tends to be monotonous without paying attention to active student participation is one of the causes of low critical thinking skills. This study aims to describe the learning process using interactive Wordwall media with a problem based learning (PBL) learning model. The research method is Classroom Action Research (CAR) which is carried out in two cycles. This study consists of four stages, namely planning, action, observation, and reflection. Participants in grade III of SD Negeri 066055 Medan Denai, totaling 8 males and 11 females. Data collection techniques were carried out by tests, interviews, and documentation. Data collection tools used test questions, interviews, and documentation. The data analysis technique used was descriptive analysis with percentages. The results of the study showed that critical thinking skills in students increased from cycle I to cycle II. In cycle I, the results of students' critical thinking skills were classified as lacking with a percentage of 48%. Furthermore, in cycle II with a percentage of 84% with a very good category. Thus, it can be concluded that using interactive Wordwall media with the problem based learning (PBL) model can improve the critical thinking skills of grade III students of SD Negeri 066055 Medan Denai in the 2023/2024 Academic Year.